Analysis of Horror Film Content as Digital Media for Islamic Dakwah - Zikri, Afdal; Handayani, Fitri; Mirdad, Jamal (Sekolah Tinggi Agama Islam Syekh Abdur Rauf Aceh Singkil, Aceh, Indonesia, 2024)
In the midst of today's increasingly sophisticated conditions, people's awareness of religious knowledge is increasingly decreasing. For this reason, there is a need for media that can be used as a medium for conveying da'wah messages. The rise in popularity of horror films nowadays can be used as a medium for preaching. However, debates often occur regarding the permissibility of watching horror films, which also leads to people's doubts about doing this. This research aims to find out horror films as an alternative medium for preaching and the law of watching horror films in Islam. This study uses a qualitative method. Qualitative methods are methods for interpreting a meaning. This research uses this analysis approach or content analysis with the type of library study research. The results of this research found that horror films can be used as a medium for Islamic da'wah because they are able to convey religious moral values. The law of watching horror films itself is actually not recommended because it can affect many things. However, it is permissible if the matter can have more positive impacts than negative impacts. [Abstrak: Di tengah kondisi zaman saat ini yang semakin canggih kesadaran umat tentang pengetahuan beragama pun semakin menurun. Untuk itu perlu adanya media-media yang dapat digunakan sebagai media penyampaian pesan dakwah. Naik daunnya film horror saat ini bisa dimanfaatkan sebagai salah satu media dakwah. Namun seringkali terjadi perdebatan mengenai kebolehan dalam menonton film horror juga menjadi keraguan umat dalam mengerjakan perkara tersebut. Penelitian ini bertujuan untuk mengetahui film horror sebagai alternatif media dakwah dan hukum menonton film horror dalam Islam. Penelitian ini menggunakan metode kualitatif. Metode kualitatif adalah metode untuk menginterprestasi suatu makna. Penelitian ini menggunakan pendekatan analisis ini atau analisis konten dengan jenis penelitian studi pustaka. Hasil penelitian ini menemukan bahwa film horror dapat dijadikan sebagai media dakwah Islam karena mampu mengantarkan nilai-nilai moral agama. Hukum menonton film horror sendiri sebenarnya adalah tidak disanrankan karena dapat mempengaruhi pada banyak hal. Namun di perbolehkan apabila perkara tersebut dapat memberikan lebih banyak dampak positif daripada dampak negatifnya.]